Development of fiber-based active thermal infrared camouflage textile. (September 2020) - Lim, Taekyung; Jeong, Sang-Mi; Seo, Keumyoung; Pak, Jeong Hyeok; Choi, Yong Kyu; Ju, Sanghyun
Graphical abstract: Highlights: Infrared camouflaging and disguise technology is used to hide-camouflage objects. Infrared emitting fibers display infrared disguise and camouflage images. Full-color infrared image is produced by generating three different IR intensities. Dynamic and static infrared images of the wearable garment were displayed. Infrared images are automatically adjusted against changing surrounding backgrounds. Abstract: The implementation of complete infrared (IR) camouflaging/disguise technology requires three-dimensional (3D) thermal camouflage that can respond rapidly to changes in the ambient temperature and operate uniformly at various angles. In this study, a fiber-based IR conductive material was developed that responds sensitively and rapidly to changes in the ambient temperature. Moreover, the material can be woven into various patterns, enabling the IR camouflage of a 3D wearable garment. A full-color IR radiation image is produced by generating three different IR intensities based on the voltage applied to a far-IR fiber. The use of passive camouflage technology enables objects to be hidden from their backgrounds, while active camouflage technology permits objects to be camouflaged against changing surrounding backgrounds or to be recognized as arbitrary objects (e.g., car, animal, or plant). It is expected that this differentiated camouflaging/disguise technology based on IR imaging can be applied to various industrial, military, and new scientific fields.